2020
DOI: 10.2147/jaa.s274245
|View full text |Cite
|
Sign up to set email alerts
|

<p>Frequency of Tiotropium Bromide Use and Clinical Features of Patients with Severe Asthma in a Real-Life Setting: Data from the Severe Asthma Network in Italy (SANI) Registry</p>

Abstract: Purpose Patients with uncontrolled asthma despite high doses of inhaled corticosteroid therapy plus another controller are defined as severe asthmatics. Tiotropium bromide respimat (TBR) is the only long-acting muscarinic antagonists (LAMA) approved for severe asthma. The aim of this study was to explore the frequency of severe asthmatics treated with TBR and characterize their clinical features in a real-life, registry-based setting. Materials and Methods Baseline data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A retrospective observational study demonstrated that severe asthmatics under treatment with LAMAs used to experience significantly worse asthma control and worse disease-related quality of life before LAMA initiation, based on the results of ACT, ACQ, and AQLQ [ 10 ]. These patients tended to be ex-smokers and had later-onset asthma in comparison to patients who did not receive LAMAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective observational study demonstrated that severe asthmatics under treatment with LAMAs used to experience significantly worse asthma control and worse disease-related quality of life before LAMA initiation, based on the results of ACT, ACQ, and AQLQ [ 10 ]. These patients tended to be ex-smokers and had later-onset asthma in comparison to patients who did not receive LAMAs.…”
Section: Discussionmentioning
confidence: 99%
“…These patients tended to be ex-smokers and had later-onset asthma in comparison to patients who did not receive LAMAs. Moreover, they were often diagnosed with concomitant bronchiectasis and used to receive oral corticosteroid (OCS) treatment courses and long-term treatment with monoclonal antibodies more frequently compared with non-LAMAusers [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ad hoc CRF on the Web platform, REDCap, has been created. A similar database has been adopted by the Severe Asthma Network Italy (SANI), which is an ongoing project (16)(17)(18)(19)(20)(21)(22)(23)(24). Each center that participates in the MANI study will have a username and password, which allows access to a reserved area of the Web application.…”
Section: Methodsmentioning
confidence: 99%
“…Particular attention is paid to the follow-up of patients in order to assess the natural history of the disease, the cost/benefit of new biological products, the adherence to therapy and the presence of particular disease biomarkers (8). 698 patients were enrolled by March 2019 (11). Bilò et al published in this issue of the Journal the findings about the most recent and currently largest registry in Italy, the IRSA (9).…”
mentioning
confidence: 99%